Culture and international innovation: a theoretical approach - Zhang-Zhang, Yingying; Rohlfer, Sylvia (Management decision, 2024)
PurposeThe rapidly changing international business landscape, driven by dynamic factors such as technology, emerging markets, and unpredictable crises, demands that organizations innovate to survive while gaining and sustaining competitive advantages. Culture, an intricate multilevel construct, presents challenges for transnational enterprises and international business as a key “soft” element of organizational strategy.Design/methodology/approachThis paper employs a triangulated method combining a systematic literature search, machine learning, and qualitative thematic content analysis to explore the relationship between culture and innovation within the context of international business. The analysis involved scrutinizing 697 journal articles indexed in the Web of Science database.FindingsUsing k-means, which is an unsupervised machine-learning tool in Python, and hypertext preprocessor language scripting, we identified seven topic clusters and 94 keywords. Qualitative thematic content analysis facilitated the recognition of prevailing patterns in researchers' conceptualizations of the interplay between innovation and culture. We identified influential relationships between cultural configurations and innovation.Research limitations/implicationsOur analysis contributes to developing a comprehensive research field map encompassing international business, innovation, and culture.Originality/valueThis study significantly enhances our knowledge of culture and international innovation. Future research that recognizes culture as a dynamic configuration at multiple levels (e.g. national, organizational, professional, and individual) and employs more comprehensive measures of innovation and culture could substantially advance our understanding of the intersection of culture and innovation in international business.